Characteristics of breaststroke skill in elite swimmers detected by means of a speed meter - Yoshimura, Y.; Tanaka, T.; Oishi, K.; Yasukawa, M.; Funato, K. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
A speed meter that measures subject's moving velocity by puling a fine wire over a generator (Maglischo, 2003) for a distance of 25 m was developed for use with competitive swimmers. In this study, the authors used the speed meter to measure the skill of three female competitive breaststroke swimmers. The velocity curves were compared for one swimmer of international achievement, one who had reached the national, but not international level, and one swimmer who was a member of a University collegiate team but had not reached the national or international levels. Methods The breaststroke was chosen for this study because the range of intracyclic velocities is greater in it than for any other competitive stroke. The wire line of the speed meter was attached to swimmers by means of a belt and their intracyclic velocity changes were recorded precisely for several stroke cycles at speeds ranging from slow to maximum. The velocity changes within one stroke cycle were then compared for efficiency among the group of subjects (Fig. 1, 2 ). Results/Discussion A comparison of velocity curves showed that the mean maximum velocity during one stroke was greatest for the international swimmer. The difference in velocity between the international swimmer and the other two subjects became greater as the athletes swam faster. Therefore, a portion of the differences in swimming speed between these three breaststroke swimmers may be accounted for by differences in their peak velocities during each stroke cycle. The mean minimum velocity during each stroke cycle was also greater for the international level swimmer when compared to the lower level competitors. In some trials, the minimum velocity within each stroke cycle slowed almost to 0 for the national and collegiate subjects, but not for the international swimmer. This was true regardless of swimming speed. Therefore, it was suggested that improvements in breaststroke performance are dependent upon improving both the maximum and minimum velocities within each stroke cycle. For all subjects, the velocity curves demonstrated that there were two propulsive peaks within each stroke cycle. These peaks corresponded to the backward thrust of the swimmers` legs and to the backward pull of their arms. The similarities between the maximum and minimum velocities from one stroke cycle to the next were also studied for each swimmer. The standard errors (SEs) of the differences for maximum and minimum velocities were calculated for each subjects' best trial. There was a tendency for the SEs to become smaller for the most skilled swimmer versus the lesser skilled swimmers. Conclusion The following conclusions were drawn from the data in this study; (1) intracyclic velocity changes can be analyzed precisely with the speed meter, (2) the highest level swimmer had the greatest maximum and minimum velocities. during each stroke cycle, and, (3) the velocity patterns for each stroke cycle were more similar from stroke to stroke for the international swimmer than they were for the lower-achieving athletes, (4) the maximum and minimum velocities within each stroke cycle were greater for the international level swimmer than for the two slower swimmers.